Causal associations between iron deficiency anemia and digestive system cancers: evidence from a bidirectional two-sample Mendelian randomization study - Yan Qin; Rong Zhou (Discover Oncology)
Abstract Background & Aims Iron deficiency anemia (IDA) is associated with digestive system cancers (DSCs), but the causal relationship is poorly understood. This two-sample bidirectional Mendelian randomization (MR) study investigated the causal association between IDA and five types of DSCs. Methods This study pooled data from a genome-wide association study of IDA (6,087 cases and 211,115 controls of European ancestry) and DSCs. IVW, weighted median, weighted mode, and MR-Egger regression were used to assess causal associations between IDA and DSCs. Sensitivity analysis included Cochran’s Q test for heterogeneity, MR-PRESSO for pleiotropy, and leave-one-out method for robustness. Results The MR analysis used 12 single-nucleotide polymorphisms (SNPs) associated with IDA as instrumental variables (IVs). In contrast, the reverse MR analysis used 20 SNPs associated with the five types of DSC as IVs. Genetic predictions revealed no significant association between IDA and the risk of DSCs: (odds ratio [OR]: 1.00; 95% confidence interval [CI] [0.76, 1.31]; P = 0.979), esophageal (OR: 0.94; 95% CI [0.67, 1.31]; P = 0.699), pancreatic (OR: 1.14; 95% CI [0.68, 1.92]; P = 0.615), liver (OR: 1.12; 95% CI [0.51, 2.47]; P = 0.776), and stomach (OR: 1.04; 95% CI [0.71, 1.54]; P = 0.830) cancers. Reverse MR also indicated no causal association between DSC and IDA. MR-Egger regression showed minimal heterogeneity impact except for colorectal cancer (heterogeneity P = 0.002). MR-PRESSO identified no outliers. Conclusion The present MR analysis shows no causal associations between IDA and the risk of DSCs.